Membangunkan Model Kompetensi Nilai Sosial bagi Program Perantisan Sistem Dual: Aplikasi Interpretive Structural Modeling (ISM) (Sains Humanika, 2018)
Â This study was conducted to develop a social values competency model for a dual system of apprenticeship programs. This model can be used as a guideline by instructors in public and private training centers that conducted programs under the Department of Skills Development in Malaysia. This model was developed based on the agreement of 13 experts. Panel of experts appointed represent the curriculum developer; the Department of Skills Development senior officer; senior lecturer; coach; skills trainers in public or private training centers; and coordinator in companies and public or private training centers. Interpretive Structural Modeling (ISM) was applied in the development of this model. Six major steps involved in the development of the model is to start by identifying the key components and elements of social values that are relevant, establish relationships between variables, develop a structural self-interaction matrix (SSIM), generating a model of the ISM, presentation of model studies and final step involves presentation and amendment to the final model study. A total of 15 elements identified by experts for the implementation of social values competency dual system of apprenticeship programs. The developed model can give a clear picture with regard to the priority that should be addressed by each instructor skills in carrying out teaching activities more meaningful.
Keywords: coach; dual system of apprenticeship programs; Interpretive Structural Modelling (ISM); skills trainer; social values